Anorectal malformations - de Blaauw, Ivo; Stenström, Pernilla; Yamataka, Atsuyuki; Miyake, Yuichiro; Reutter, Heiko Martin; Midrio, Paola; Wood, Richard; Grano, Caterina; Pakarinen, Mikko (Nature Reviews Disease Primers, 2024)
Anorectal malformations (ARM) are rare congenital anomalies with an overall prevalence of 3.32 per 10,000 pregnancies. ARM describe a spectrum of anomalies of the anus and rectum ranging from a minimally displaced anal canal to a complete fusion of the anorectum, vagina and urethra with hypoplastic sphincter and pelvic floor muscle. Aberrant septation of the hindgut with anomalous cloacal membrane during weeks 6 to 9 of gestation form the developmental basis for a spectrum of anomalies defined as ARM. Although underlying specific syndromes and occasional familiar occurrence suggest genetic aetiology, most ARM are non-syndromic and their causal genetic mechanisms and non-genetic insults remain unclear. ARM is a clinical diagnosis, generally made early after birth via careful inspection of the perineum. Prenatal detection remains rare, and modern technical developments have added little to prenatal diagnostics. ARM is corrected surgically. Since its introduction in 1982, posterior sagittal anorectoplasty is the most common surgery for ARM reconstruction. Subsequent surgical adaptations focus on minimizing iatrogenic operative injury by limiting surgical invasiveness. They include laparoscopic procedures and shortening of incisions with confined dissection in open surgery. Although outcomes in patients with ARM have evolved throughout the past decades, there is urgent need for further improvements both in functional outcomes and quality of life. The importance of psychosocial experiences of affected patients is increasingly recognized. Continued research is necessary to improve prenatal detection, to elucidate genetic and epigenetic alterations and to refine optimal surgical procedures.
CRIS-Team Scopus Importer:2024-11-29